"I made myself small like a cat and ran away": workplace sexual harassment, precarious immigration status and legal violence. Issue 6 (18th August 2019) - Villegas, Paloma E.
ABSTRACT: This article examines the intersection between workplace sexual harassment, immigration status, and insecure employment status ('precarious work'). Although a rich body of literature explores how gender impacts all three fields independently, less is known about how they interact. Drawing on narratives from migrant women with precarious immigration status in Toronto, Canada, I propose that experiences of sexual harassment illuminate the workings of migrant illegalization through 'legal violence'. Furthermore, findings demonstrate that precarious status migrant women do not experience sexual harassment in isolation; other axes of oppression interlock to exacerbate it. Despite this, precarious status migrant women negotiate their experiences, sometimes enduring sexual harassment; referred to here as aguantar, and sometimes resisting it explicitly.